2023
DOI: 10.1038/s41467-023-38113-4
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia relapse via genetic immune escape after allogeneic hematopoietic cell transplantation

Abstract: Graft-versus-leukemia (GvL) reactions are responsible for the effectiveness of allogeneic hematopoietic cell transplantation as a treatment modality for myeloid neoplasia, whereby donor T- effector cells recognize leukemia neoantigens. However, a substantial fraction of patients experiences relapses because of the failure of the immunological responses to control leukemic outgrowth. Here, through a broad immunogenetic study, we demonstrate that germline and somatic reduction of human leucocyte antigen (HLA) he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…Conversely, the allelic loss and lower expression of HLA in +6 AML may imply a dichotomy of mechanisms by which +6 contributes to advanced leukemia vs bone marrow failure. Further evidence of allelic deletion of HLA genes in +6 AML points toward immune escape and evasion, a mechanism already described in relapsing AML under immune pressure [ 5 ] and potentially contributing to the transformation of AA to malignant disease in this series.…”
Section: To the Editorsupporting
confidence: 58%
See 1 more Smart Citation
“…Conversely, the allelic loss and lower expression of HLA in +6 AML may imply a dichotomy of mechanisms by which +6 contributes to advanced leukemia vs bone marrow failure. Further evidence of allelic deletion of HLA genes in +6 AML points toward immune escape and evasion, a mechanism already described in relapsing AML under immune pressure [ 5 ] and potentially contributing to the transformation of AA to malignant disease in this series.…”
Section: To the Editorsupporting
confidence: 58%
“…Along with somatic mutations in various HLA alleles, deletions of various sizes including microdeletions of the HLA locus as well as somatic UPD6p have been suggested to result from immune pressure and to act as means of escape hematopoiesis in immune-mediated aplastic anemia (AA) [ 3 , 4 ]. Similarly, our group described these lesions in the context of loss of graft versus leukemia (GvL) effect of mismatched donor HLA alleles following allogeneic hematopoietic stem cell transplant (alloHSCT) with subsequent relapse of myeloid leukemias [ 5 ]. We further demonstrated that the enrichment of specific amino acids within the peptide-binding groove of HLA class II, especially HLA-DRB1, affects its interaction with the T-cell receptor (TCR) and hence underlies the autoreactivity inherent to autoimmune AA [ 6 ].…”
Section: To the Editormentioning
confidence: 99%
“…These mutations can act as confounding factors in genetic association studies, particularly when de novo variants confer a significant clonal advantage. Somatic mutations in HLA genes have been identified in patients with solid and hematological cancers ( 38 , 39 ); in hematological cancer recipients of allogeneic and haploidentical stem cell transplantation ( 39 , 40 ); and in patients with aplastic anemia ( 41 ). The significance of these mutations lies in their provision of a selective advantage to the mutated clones, enabling them to evade immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Newly developed, highly affine CAR-T cells have the ability to target even low antigen-expressing cells ( 158 ) and overcome epitope masking. The application of these T cells could help to target AML cells in patients after allo-HSCT with relapsed disease due to immune escape ( 159 ).…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%